Human immunodeficiency virus–related peripheral neuropathy: A systematic review and meta‐analysis. (14th December 2020) - Julian, Thomas; Rekatsina, Martina; Shafique, Faiza; Zis, Panagiotis
Abstract: Background and purpose: Human immunodeficiency virus (HIV)‐associated neurological syndromes occur in affected individuals as a consequence of primary HIV infection, opportunistic infections, inflammation and as an adverse effect of some forms of antiretroviral treatment (ART). The aim of this systematic review was to establish the epidemiological characteristics, clinical features, pathogenetic mechanisms and risk factors of HIV‐related peripheral neuropathy (PN). Methods: A systematic, computer‐based search was conducted using the PubMed database. Data regarding the above parameters were extracted. Ninety‐four articles were included in this review. Results: The most commonly described clinical presentation of HIV neuropathy is the distal predominantly sensory polyneuropathy. The primary pathology in HIVPN appears to be axonal rather than demyelinating. Age and treatment with medications belonging in the nucleoside analogue reverse transcriptase class are risk factors for developing HIV‐related neuropathy. The pooled prevalence of PN in patients naïve to ARTs was established to be 29% (95% CI: 9%–62%) and increased to 38% (95% confidence interval [CI]: 29%–48%) when looking into patients at various stages of their disease. More than half of patients with HIV‐related neuropathy are symptomatic (53%, 95% CI: 41%–63%). Management of HIV‐related neuropathy is mainly symptomatic, although there is evidence that discontinuation of some types of ART, such as didanosine, can improve or resolve symptoms. Conclusions: Human immunodeficiency virus–related neuropathy is common and represents a significant burden in patients' lives. Our understanding of the disease has grown over the last years, but there are unexplored areas requiring further study.